Neutrophils impose strong immune pressure against PfEMP1 variants implicated in cerebral malaria. (13th April 2022) - Zelter, Tamir; Strahilevitz, Jacob; Simantov, Karina; Yajuk, Olga; Adams, Yvonne; Ramstedt Jensen, Anja; Dzikowski, Ron; Granot, Zvi
Abstract: Plasmodium falciparum, the deadliest form of human malaria, remains one of the major threats to human health in endemic regions. Its virulence is attributed to its ability to modify infected red blood cells (iRBC) to adhere to endothelial receptors by placing variable antigens known as PfEMP1 on the iRBC surface. PfEMP1 expression determines the cytoadhesive properties of the iRBCs and is implicated in severe malaria. To evade antibody‐mediated responses, the parasite undergoes continuous switches of expression between different PfEMP1 variants. Recently, it became clear that in addition to antibody‐mediated responses, PfEMP1 triggers innate immune responses; however, the role of neutrophils, the most abundant white blood cells in the human circulation, in malaria remains elusive. Here, we show that neutrophils recognize and kill blood‐stage P. falciparum isolates. We identify neutrophil ICAM‐1 and specific PfEMP1 implicated in cerebral malaria as the key molecules involved in this killing. Our data provide mechanistic insight into the interactions between neutrophils and iRBCs and demonstrate the important influence of PfEMP1 on the selective innate response to cerebral malaria. SYNOPSIS: As first line of defense against severe malaria, neutrophils recognize specific PfEMP1 molecules on the infected erythrocyte via ICAM‐1. This ligand‐receptor interaction leads to efficient killing of Plasmodium falciparum parasites associated with cerebral malaria. Neutrophils kill blood stage P. falciparum by phagocytosis of infected erythrocytes and targeted oxidative burst. Neutrophil's ICAM‐1 and parasite's PfEMP1 are important mediators of neutrophil interactions with infected erythrocytes. Neutrophils impose strong selective pressure against parasites expressing PfEMP1. Abstract : As first line of defense against severe malaria, neutrophils recognize specific PfEMP1 molecules on the infected erythrocyte via ICAM‐1. This ligand‐receptor interaction leads to efficient killing of Plasmodium falciparum parasites associated with cerebral malaria.